THE EFFECT OF LEVERAGE, PROFITABILITY, CAPITAL INTENSITY AND CORPORATE GOVERNANCE ON TAX AVOIDANCE - Sari Mustika Widyastuti; Inten Meutia; Aloysius Bagas Candrakanta (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
This study was conducted to analyze and test and provide empirical evidence of the effect of profitability, leverage, corporate governance, and capital intensity on tax avoidance. The population in this study were companies in the agricultural and mining sectors which were listed on the Indonesia Stock Exchange for the period 2015-2019. The data selection technique used was purposive sampling to obtain 270 companies. The analytical method used is multiple linear regression. The test results show that the variable profitability, leverage has a positive effect on tax avoidance. The board of commissioners and the audit committee as a proxy for corporate governance and the capital intensity variable also shows a positive influence on tax avoidance.